Human well-being and economic goals - Ackerman, Frank, ed.; Kiron, David, ed.; Goodwin, Neva R., ed.; Harris, Jonathan M., ed. (Washington : Island Press, 1997)
Economics
Keywords: Welfare economics; Values; Utility theory; National development